A low-n-hexane extract content HDPE hollow resin, its preparation method and hollow product
Patent Information
- Application Number
- CN202610847116.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-12
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-06-12
AI Technical Summary
按照这类常规工艺制备的HDPE中空树脂,正己烷提取物含量往往仍维持在较高水平,难以满足高洁净度包装领域对低迁移物含量的要求
[0057] 1. This invention uses chromium acetate, chromium titanate and trifluoroacetic acid/perfluorooctanoic acid combined fluorine modifiers to be loaded on a silica support to prepare fluorine-modified chromium metal active center catalysts. This is beneficial to adjust the active center state of the catalyst and reduce the content of low molecular weight fractions and n-hexane extract from the polymerization source.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polyethylene resin technology, specifically relating to a low-hexane extract content HDPE hollow resin, its preparation method, and hollow products. Background Technology
[0002] HDPE hollow resin is widely used in hollow packaging bottles and drums for food, beverages, edible oils, daily chemicals, pharmaceuticals, and cosmetics. With increasingly stringent safety requirements for food contact materials, market focus on HDPE hollow resin has expanded from traditional indicators such as density, melt flow rate, and mechanical properties to the content of migratable low-molecular-weight substances in the resin. If the content of oligomers or extractable substances produced during processing is too high, they may gradually migrate and precipitate out during long-term contact with the contents, affecting the quality of the contents and posing hygiene and safety risks. Therefore, developing HDPE hollow resin with low n-hexane extract content is of significant practical importance.
[0003] Existing technologies have disclosed various solutions for improving the properties of polyethylene resin. For example, controlling the resin's molecular weight, density, type of comonomer, and polymerization reaction conditions can improve the environmental stress cracking resistance and processing performance of hollow products; improvements can be made to catalyst activity, comonomer distribution, or thermal processing stability from the perspectives of catalyst preparation, polymerization process control, or the formulation of processing stabilizing agents. However, these technical solutions mainly focus on improving traditional physical and mechanical properties or processing performance, rather than systematically controlling the content of oligomers and n-hexane extracts in the resin at its source.
[0004] For packaging applications with high hygiene requirements, simply meeting processing and mechanical performance standards is insufficient. The existing technologies mentioned above do not focus on reducing the concentration of oligomers already present in the resin or controlling the increase in extractable content during processing. Even when catalyst treatment or antioxidant application is involved, they lack effective suppression of the formation of low molecular weight fractions. HDPE hollow resins prepared using these conventional processes often retain a high level of hexane extract content, making it difficult to meet the low migration requirements of high-cleanliness packaging applications.
[0005] Therefore, there is an urgent need to develop a preparation method that can effectively reduce the amount of oligomers generated and the content of n-hexane extract in HDPE hollow resin from the source, so that the resin can meet the application needs of packaging fields with high hygiene requirements such as food, medicine, and cosmetics while maintaining good processing performance and mechanical properties. Summary of the Invention
[0006] To address the shortcomings of existing technologies, this invention proposes a low-hexane extract content HDPE hollow resin, its preparation method, and hollow product. This invention provides an innovative solution for reducing the oligomer content and hexane extract content of HDPE hollow resin by constructing a fluorinated chromium acetate / chromium titanate composite chromium metal active center catalyst modified with a combination of trifluoroacetic acid and perfluorooctanoic acid, coupled with high-temperature precise temperature-controlled activation, non-reduction treatment, and a two-stage narrow-temperature controlled polymerization process.
[0007] The first objective of this invention is achieved through the following technical solution:
[0008] A method for preparing HDPE hollow resin with low n-hexane extract content includes the following steps:
[0009] (1) Using silica as a carrier, chromium acetate, chromium titanate and fluorine modifier are loaded onto the silica to obtain a catalyst precursor; the fluorine modifier is a combination of trifluoroacetic acid and perfluorooctanoic acid; The catalyst precursor was calcined and activated to obtain a fluorine-modified chromium metal active center catalyst. (2) In the presence of the fluorine-modified chromium metal active center catalyst, ethylene and 1-hexene are supplied to a first-stage reactor for first-stage polymerization to obtain a first-stage polymerization product; the first-stage polymerization product is fed into a second-stage reactor, and ethylene and 1-hexene are supplied to the second-stage reactor for second-stage polymerization. The second-stage polymerization temperature is set 1-3°C lower than the first-stage polymerization temperature to obtain a polymer resin. The temperature control accuracy for both the primary polymerization and the secondary polymerization is ±0.5℃. (3) Granulate the polymer resin to obtain the HDPE hollow resin with low n-hexane extract content.
[0010] The HDPE hollow resin is high-density polyethylene (HDPE) resin used for hollow blow molding.
[0011] Preferably, in step (1), the mass ratio of chromium acetate to chromium titanate is 1:10-1:30.
[0012] More preferably, the mass ratio of chromium acetate to chromium titanate is 1:15-1:20.
[0013] Preferably, the catalyst precursor is activated by calcination at 800-880°C.
[0014] Preferably, in step (1), the total amount of chromium in chromium acetate and chromium titanate is 0.3-1.0 wt% of the mass of silicon dioxide.
[0015] Preferably, in step (1), the mass ratio of trifluoroacetic acid to perfluorooctanoic acid is 1:1 to 1:5.
[0016] Preferably, in step (1), the total fluorine content in the fluorine modifier is 0.03-0.07 wt% based on the mass of silicon dioxide.
[0017] Preferably, in step (1), the silicon dioxide is a 10-50 μm porous SiO2 powder.
[0018] More preferably, the silica is pre-calcined before loading chromium acetate, chromium titanate, and fluorine modifier.
[0019] More preferably, the silicon dioxide is pre-calcined at 700-900°C for 3-5 hours.
[0020] More preferably, the silicon dioxide is pre-calcined and then transferred to an impregnation vessel to cool naturally to room temperature.
[0021] Preferably, in step (1), the chromium acetate, chromium titanate, and fluorine modifier are dispersed in an inert solvent and then mixed with silica for impregnation.
[0022] More preferably, the inert solvent is selected from one or more of tetrahydrofuran and hexane.
[0023] More preferably, the immersion time is 12-24 hours.
[0024] A further preferred embodiment is that after impregnation, the catalyst is dried at 70-80°C for 4-6 hours to obtain the catalyst support.
[0025] Preferably, in step (1), the calcination activation time is 5-8 hours.
[0026] Preferably, the amount of the fluorine-modified chromium metal active center catalyst added is 0.025-0.04 wt% based on the total amount of ethylene and 1-hexene fed.
[0027] Preferably, the polymerization temperature is set at 70-90℃.
[0028] Preferably, in the first-stage polymerization, the amount of 1-hexene added is 0.3-0.6 mol, based on the total molar amount of ethylene and 1-hexene supplied to the first-stage reactor.
[0029] More preferably, in the two-stage polymerization, the amount of 1-hexene added is 0.8-1.2 mol, based on the total molar amount of ethylene and 1-hexene supplied to the two-stage reactor.
[0030] Preferably, the ratio of the total molar amount of ethylene and 1-hexene supplied to the first stage reactor to the total molar amount of ethylene and 1-hexene supplied to the second stage reactor is 1:1 to 1:3.
[0031] Preferably, in step (2), before a polymerization step, the fluorine-modified chromium metal active center catalyst is mixed with isobutane, and the amount of the fluorine-modified chromium metal active center catalyst added is 300-600 g / L based on the volume of isobutane.
[0032] Preferably, in step (2), the first-stage polymerization product is flash-evaporated and then fed into the second-stage reactor.
[0033] Preferably, in step (3), the granulation process further includes a post-processing step, which includes flash evaporation, deactivation and drying.
[0034] Preferably, in step (3), an antioxidant system is added before granulation.
[0035] More preferably, the antioxidant system comprises any one or more of hindered phenolic antioxidants and hydroxylamine antioxidants.
[0036] More preferably, the amount of antioxidant system added is 0.05-0.08 parts by weight, based on 100 parts by weight of the polymerized resin.
[0037] More preferably, when the antioxidant system contains both hindered phenolic antioxidants and hydroxylamine antioxidants, the mass ratio of the hindered phenolic antioxidants to the hydroxylamine antioxidants is 10:1 to 10:5.
[0038] In a further preferred embodiment, the mass ratio of the hindered phenolic antioxidant to the hydroxylamine antioxidant is 10:1 to 10:2.
[0039] More preferably, the hydroxylamine antioxidant is N,N-bis(n-octadecane)hydroxylamine (antioxidant FSO42).
[0040] More preferably, the hindered phenolic antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (antioxidant 1010).
[0041] Preferably, in step (3), the granulation temperature is 190-230℃.
[0042] In this scheme, chromium acetate and chromium titanate serve as the source of chromium metal active centers. These are combined with a fluorinated modifier composed of trifluoroacetic acid and perfluorooctanoic acid, supported on a silica carrier. Activation is achieved through high-temperature calcination at 800-880℃, with precise temperature control within ±0.3℃. This process facilitates the formation of fluorinated chromium metal active centers suitable for ethylene polymerization. No reduction treatment is performed after calcination activation, avoiding the adverse effects of reduction on the active center state and allowing the catalyst to more effectively reduce the hexane extract content of the resin product during polymerization.
[0043] Furthermore, this scheme employs a two-stage polymerization process with narrow-range temperature control for both stages. The first-stage polymerization is set at 70-90℃, while the second-stage polymerization is set at 1-3℃ lower, with both stages maintaining a temperature control accuracy of ±0.5℃. This differentiated and precise temperature control allows for segmented regulation of chain growth and molecular chain formation at different polymerization stages, reducing the risk of increased low-molecular-weight components due to temperature fluctuations.
[0044] Meanwhile, this scheme controls the amount of 1-hexene added in both the first-stage and second-stage polymerization processes. The amount of 1-hexene added in the first-stage polymerization is 0.3-0.6 mol%, and in the second-stage polymerization, it is 0.8-1.2 mol%. By adding 1-hexene in stages with lower amounts in the first stage and higher amounts in the second, the comonomers achieve a more suitable distribution at different polymerization stages. This helps to balance the resin's molecular weight distribution, branching distribution, processing performance, and mechanical properties, while reducing the hexane extract content in the resin product.
[0045] HDPE hollow resin is obtained after polymerization, post-treatment, and granulation. Post-treatment can reduce the impact of residues on resin quality and stability; an antioxidant system can be added before granulation to improve the thermo-oxidative stability of the resin during processing and reduce the further formation of low-molecular-weight substances during granulation and subsequent processing.
[0046] The second objective of this invention is achieved through the following technical solution:
[0047] An HDPE hollow resin is prepared by any of the preparation methods described above.
[0048] Preferably, the density of the HDPE hollow resin is 0.952-0.956 g / cm³. 3 .
[0049] Preferably, the melt flow rate of the HDPE hollow resin is 0.16-0.26 g / 10 min.
[0050] Preferably, the tensile yield stress of the HDPE hollow resin is ≥22MPa, and the nominal strain at tensile break is ≥400%.
[0051] Preferably, the hexane extract content of the HDPE hollow resin is <0.5wt%.
[0052] More preferably, the hexane extract content of the HDPE hollow resin is <0.45wt%.
[0053] The third objective of this invention is achieved through the following technical solution:
[0054] A hollow product comprising the above-mentioned HDPE hollow resin.
[0055] Preferably, the hollow product can be a bottle, barrel, or other hollow packaging product for food, beverage, purified water, edible oil, daily chemical, pharmaceutical, or cosmetic packaging.
[0056] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0057] 1. This invention uses chromium acetate, chromium titanate and trifluoroacetic acid / perfluorooctanoic acid combined fluorine modifiers to be loaded on a silica support to prepare fluorine-modified chromium metal active center catalysts. This is beneficial to adjust the active center state of the catalyst and reduce the content of low molecular weight fractions and n-hexane extract from the polymerization source.
[0058] 2. In this invention, the catalyst precursor is activated by high-temperature calcination at 800-880℃, and the calcination activation temperature is controlled with an accuracy of ±0.3℃. Furthermore, no reduction treatment is performed after calcination activation, which is beneficial for the stable formation of suitable catalytic active centers and reduces the adverse effects of reduction treatment on the state of active centers and the structure of polymerization products.
[0059] 3. The present invention adopts a two-stage narrow temperature control polymerization process, which controls the set temperature of the second stage polymerization to be 1-3℃ lower than that of the first stage polymerization, and makes the temperature control accuracy of both stages ±0.5℃, which can reduce the adverse effects of polymerization temperature fluctuations on molecular weight distribution and the formation of low molecular weight fractions.
[0060] 4. In the two-stage polymerization, the present invention adopts a segmented control method of low 1-hexene addition in the first stage and high 1-hexene addition in the second stage, so that the comonomers are appropriately distributed in different polymerization stages, which is beneficial to improving the resin molecular chain structure and reducing the content of n-hexane extract while maintaining processing performance and mechanical properties.
[0061] 5. This invention utilizes the synergistic effects of fluorine-modified composite chromium catalyst, high-temperature precise temperature control non-reductive activation, two-stage narrow temperature control polymerization, and the segmented addition of 1-hexene to produce HDPE hollow resin with a low n-hexane extract content, making it suitable for hollow packaging applications with high hygiene requirements, such as food, beverages, edible oils, pharmaceuticals, cosmetics, and daily chemical products. Detailed Implementation
[0062] The following will provide a clear and complete description of the concept, specific structure, and technical effects of the present invention in conjunction with embodiments, so as to fully understand the purpose, solution, and effects of the present invention. It should be noted that, unless otherwise specified, the embodiments and features described in the embodiments of the present invention can be combined with each other.
[0063] The materials used in the embodiments and comparative examples of this invention are described below:
[0064] Silica: 15-25μm porous SiO2 powder; purchased from Grace Company, USA.
[0065] Isobutane: purity > 90 wt%; purchased from Shandong Yuean Chemical Co., Ltd.
[0066] Ethylene: purity > 99.8 wt%; purchased from Zhejiang Petrochemical Co., Ltd.
[0067] 1-Hexene: Purity > 99.2 wt%; purchased from Zhejiang Petrochemical Co., Ltd.
[0068] The present invention will be further illustrated by specific embodiments below, but the scope of protection of the present invention is not limited thereto.
[0069] Example 1
[0070] The HDPE hollow resin in Example 1 was prepared using the following steps:
[0071] (1) Under nitrogen protection, SiO2 porous powder was fed into a calcination furnace and calcined at 800°C for 4 hours. After calcination, SiO2 porous powder was transferred to an impregnation vessel and cooled naturally to room temperature.
[0072] (2) Chromium acetate and chromium titanate were weighed according to a mass ratio of chromium acetate to chromium titanate of 1:15, and the total amount of chromium in chromium acetate and chromium titanate, calculated as chromium element, was controlled to be 0.5 wt% of the mass of SiO2 porous powder; trifluoroacetic acid and perfluorooctanoic acid were weighed according to a mass ratio of trifluoroacetic acid to perfluorooctanoic acid of 1:2, and the total fluorine content was controlled to be 0.05 wt%. Chromium acetate, chromium titanate, trifluoroacetic acid and perfluorooctanoic acid were added to a mixed solution of tetrahydrofuran and hexane with a volume ratio of 3:1, stirred and dispersed to obtain a dispersion.
[0073] (3) Add the SiO2 porous powder that was calcined and cooled in step (1) to the dispersion obtained in step (2), stir and disperse at 25°C and impregnate for 18h; after impregnation, dry at 75°C for 5h to obtain the catalyst support.
[0074] (4) The catalyst loading obtained in step (3) is transferred to a calcination furnace and calcined at 840°C for 6 hours. The activation temperature is controlled with an accuracy of ±0.3°C. No reduction treatment is performed after calcination activation to obtain a chromium metal active center catalyst.
[0075] (5) Weigh 0.03 wt% of the total feed mass of ethylene and 1-hexene. Then, mix the weighed chromium metal active center catalyst with isobutane solvent at a ratio of 400 g / L and feed it into a first-stage reactor. Supply ethylene and 1-hexene to the first-stage reactor for first-stage polymerization. The 1-hexene supplied to the first-stage reactor is 0.4 mol% of the total molar amount of ethylene and 1-hexene supplied to the first-stage reactor. The first-stage polymerization temperature is 75 ± 0.5 °C, and the first-stage polymerization product is obtained.
[0076] (6) The first-stage polymerization product obtained in step (5) is flash-evaporated and then fed into the second-stage reactor. Ethylene and 1-hexene are supplied to the second-stage reactor to continue the second-stage polymerization. The 1-hexene supplied to the second-stage reactor is 1.0 mol% of the total molar amount of ethylene and 1-hexene supplied to the second-stage reactor. The second-stage polymerization temperature is 73 ± 0.5 °C, and a polymer resin slurry is obtained. The ratio of the total molar amount of ethylene and 1-hexene supplied to the first-stage reactor to the total molar amount of ethylene and 1-hexene supplied to the second-stage reactor is 1:2.
[0077] (7) The polymer resin slurry obtained in step (6) is subjected to flash evaporation, deactivation and drying in sequence to obtain polymer resin powder; 1010 / FS042 composite antioxidant is added to the obtained polymer resin powder, the mass ratio of 1010 to FS042 is 10:2, and the amount of composite antioxidant added is 0.06 parts; then it is extruded and granulated at 210°C to obtain the HDPE hollow resin of Example 1.
[0078] Example 2
[0079] The HDPE hollow resin of Example 2 was prepared using the following steps. The difference between Example 2 and Example 1 is that the chromium source ratio, fluorine modifier ratio and total fluorine content are different in step (2), the catalyst calcination activation temperature is different in step (4), the two-stage polymerization temperatures and the amount of 1-hexene added are different in steps (5) and (6), and the antioxidant system ratio and addition amount are different in step (7). The other steps are the same as in Example 1.
[0080] (1) Follow the steps (1) of Example 1.
[0081] (2) Weigh chromium acetate and chromium titanate according to a mass ratio of 1:10, and weigh trifluoroacetic acid and perfluorooctanoic acid according to a mass ratio of 1:1, and control the total fluorine content to be 0.07wt%. Add chromium acetate, chromium titanate, trifluoroacetic acid and perfluorooctanoic acid to a mixed solution of tetrahydrofuran and hexane in a volume ratio of 3:1, stir and disperse to obtain a dispersion.
[0082] (3) The catalyst support was obtained by following step (3) of Example 1.
[0083] (4) The catalyst loading obtained in step (3) is transferred to a calcination furnace and calcined at 800°C for 6 hours. The activation temperature is controlled with an accuracy of ±0.3°C. No reduction treatment is performed after calcination activation to obtain a chromium metal active center catalyst.
[0084] (5) Weigh the chromium metal active center catalyst obtained in step (4) at 0.025 wt% of the total feed mass of ethylene and 1-hexene. Mix the weighed chromium metal active center catalyst with isobutane solvent at a ratio of 300 g / L and feed it into a first-stage reactor. Supply ethylene and 1-hexene to the first-stage reactor for first-stage polymerization. The 1-hexene supplied to the first-stage reactor is 0.3 mol% of the total molar amount of ethylene and 1-hexene supplied to the first-stage reactor. The first-stage polymerization temperature is 70 ± 0.5 °C, and the first-stage polymerization product is obtained.
[0085] (6) The first-stage polymerization product obtained in step (5) is flash-evaporated and then fed into the second-stage reactor. Ethylene and 1-hexene are supplied to the second-stage reactor to continue the second-stage polymerization. The 1-hexene supplied to the second-stage reactor is 0.8 mol% of the total molar amount of ethylene and 1-hexene supplied to the second-stage reactor. The second-stage polymerization temperature is 69 ± 0.5 °C, and a polymer resin slurry is obtained. The ratio of the total molar amount of ethylene and 1-hexene supplied to the first-stage reactor to the total molar amount of ethylene and 1-hexene supplied to the second-stage reactor is 1:1.
[0086] (7) The polymer resin slurry obtained in step (6) is subjected to flash evaporation, deactivation and drying in sequence to obtain polymer resin powder; 1010 / FS042 composite antioxidant is added to the obtained polymer resin powder, the mass ratio of 1010 to FS042 is 10:1, and the amount of composite antioxidant added is 0.05 parts; then it is extruded and granulated at 210°C to obtain HDPE hollow resin of Example 2.
[0087] Example 3
[0088] The HDPE hollow resin of Example 3 was prepared using the following steps. The difference between Example 3 and Example 1 is that the chromium source ratio, fluorine modifier ratio and total fluorine content are different in step (2), the catalyst calcination activation temperature is different in step (4), the two-stage polymerization temperatures and the amount of 1-hexene added are different in steps (5) and (6), and the antioxidant system ratio and addition amount are different in step (7). The other steps are the same as those in Example 1.
[0089] (1) Follow the steps (1) of Example 1.
[0090] (2) Weigh chromium acetate and chromium titanate according to a mass ratio of 1:20, and weigh trifluoroacetic acid and perfluorooctanoic acid according to a mass ratio of 1:4, and control the total fluorine content to be 0.04 wt%. Add chromium acetate, chromium titanate, trifluoroacetic acid and perfluorooctanoic acid to a mixed solution of tetrahydrofuran and hexane in a volume ratio of 3:1, stir and disperse to obtain a dispersion.
[0091] (3) The catalyst support was obtained by following step (3) of Example 1.
[0092] (4) The catalyst loading obtained in step (3) is transferred to a calcination furnace and calcined at 860°C for 6 hours. The activation temperature is controlled with an accuracy of ±0.3°C. No reduction treatment is performed after calcination activation to obtain a chromium metal active center catalyst.
[0093] (5) Weigh the chromium metal active center catalyst obtained in step (4) at 0.04 wt% of the total feed mass of ethylene and 1-hexene. Then, mix the weighed chromium metal active center catalyst with isobutane solvent at a ratio of 600 g / L and feed it into a first-stage reactor. Supply ethylene and 1-hexene to the first-stage reactor for first-stage polymerization. The 1-hexene supplied to the first-stage reactor is 0.5 mol% of the total molar amount of ethylene and 1-hexene supplied to the first-stage reactor. The first-stage polymerization temperature is 80±0.5℃, and the first-stage polymerization product is obtained.
[0094] (6) The first-stage polymerization product obtained in step (5) is flash-evaporated and then fed into the second-stage reactor. Ethylene and 1-hexene are supplied to the second-stage reactor to continue the second-stage polymerization. The 1-hexene supplied to the second-stage reactor is 1.1 mol% of the total molar amount of ethylene and 1-hexene supplied to the second-stage reactor. The second-stage polymerization temperature is 77 ± 0.5 °C, and a polymer resin slurry is obtained. The ratio of the total molar amount of ethylene and 1-hexene supplied to the first-stage reactor to the total molar amount of ethylene and 1-hexene supplied to the second-stage reactor is 1:3.
[0095] (7) The polymer resin slurry obtained in step (6) is subjected to flash evaporation, deactivation and drying in sequence to obtain polymer resin powder; 1010 / FS042 composite antioxidant is added to the obtained polymer resin powder, the mass ratio of 1010 to FS042 is 10:3, and the amount of composite antioxidant added is 0.07 parts; then it is extruded and granulated at 210°C to obtain the HDPE hollow resin of Example 3.
[0096] Example 4
[0097] The HDPE hollow resin of Example 4 was prepared using the following steps. The difference between Example 4 and Example 1 is that the proportion of chromium source, the proportion of fluorine modifier, and the total amount of fluorine are different in step (2); the catalyst calcination activation temperature is different in step (4); the polymerization temperatures of the two stages and the amount of 1-hexene added are different in steps (5) and (6); and the proportion and amount of antioxidant system added are different in step (7). The other steps are the same as those in Example 1.
[0098] (1) Follow the steps (1) of Example 1.
[0099] (2) Weigh chromium acetate and chromium titanate according to a mass ratio of 1:30, and weigh trifluoroacetic acid and perfluorooctanoic acid according to a mass ratio of 1:5, and control the total fluorine content to be 0.03wt%. Add chromium acetate, chromium titanate, trifluoroacetic acid and perfluorooctanoic acid to a mixed solution of tetrahydrofuran and hexane in a volume ratio of 3:1, stir and disperse to obtain a dispersion.
[0100] (3) The catalyst support was obtained by following step (3) of Example 1.
[0101] (4) The catalyst loading obtained in step (3) is transferred to a calcination furnace and calcined at 880°C for 6 hours. The activation temperature is controlled with an accuracy of ±0.3°C. No reduction treatment is performed after calcination activation to obtain a chromium metal active center catalyst.
[0102] (5) Weigh the chromium metal active center catalyst obtained in step (4) at 0.03 wt% of the total feed mass of ethylene and 1-hexene. Mix the weighed chromium metal active center catalyst with isobutane solvent at a ratio of 400 g / L and feed it into a first-stage reactor. Supply ethylene and 1-hexene to the first-stage reactor for first-stage polymerization. The 1-hexene supplied to the first-stage reactor is 0.6 mol% of the total molar amount of ethylene and 1-hexene supplied to the first-stage reactor. The first-stage polymerization temperature is 90 ± 0.5 °C, and the first-stage polymerization product is obtained.
[0103] (6) The first-stage polymerization product obtained in step (5) is flash-evaporated and then fed into the second-stage reactor. Ethylene and 1-hexene are supplied to the second-stage reactor to continue the second-stage polymerization. The 1-hexene supplied to the second-stage reactor is 1.2 mol% of the total molar amount of ethylene and 1-hexene supplied to the second-stage reactor. The second-stage polymerization temperature is 88±0.5℃, and a polymer resin slurry is obtained. The ratio of the total molar amount of ethylene and 1-hexene supplied to the first-stage reactor to the total molar amount of ethylene and 1-hexene supplied to the second-stage reactor is 1:2.
[0104] (7) The polymer resin slurry obtained in step (6) is subjected to flash evaporation, deactivation and drying in sequence to obtain polymer resin powder; 1010 / FS042 composite antioxidant is added to the obtained polymer resin powder, the mass ratio of 1010 to FS042 is 10:5, and the amount of composite antioxidant added is 0.08 parts; then it is extruded and granulated at 210°C to obtain the HDPE hollow resin of Example 4.
[0105] Comparative Example 1
[0106] The HDPE hollow resin of Comparative Example 1 was prepared using the following steps. The difference between Comparative Example 1 and Example 1 is that no fluorine modifier was added in step (2), while the other steps were the same as in Example 1:
[0107] (1) Follow the steps (1) of Example 1.
[0108] (2) Weigh chromium acetate and chromium titanate according to a mass ratio of 1:15, without adding trifluoroacetic acid and perfluorooctanoic acid, and the total fluorine content is 0 wt%. Add chromium acetate and chromium titanate to tetrahydrofuran and / or hexane, stir and disperse to obtain a dispersion.
[0109] (3) The catalyst support was obtained by following step (3) of Example 1.
[0110] (4) The catalyst loading obtained in step (3) is transferred to a calcination furnace and calcined at 840°C for 6 hours. The activation temperature is controlled with an accuracy of ±0.3°C. No reduction treatment is performed after calcination activation to obtain a chromium metal active center catalyst.
[0111] (5-7) Following the steps (5-7) of Example 1, HDPE hollow resin of Comparative Example 1 was obtained.
[0112] Comparative Example 2
[0113] The HDPE hollow resin of Comparative Example 2 was prepared using the following steps. The difference between Comparative Example 2 and Example 1 is that the catalyst was calcined and activated in step (4) and then subjected to reduction treatment. The other steps are the same as in Example 1:
[0114] (1-3) The catalyst support was obtained by following the steps (1-3) of Example 1.
[0115] (4) The catalyst loading obtained in step (3) is transferred to a calcination furnace and calcined and activated at 840°C for 6 hours. The activation temperature is controlled with an accuracy of ±0.3°C. After calcination and activation, a reduction treatment is performed to obtain a chromium metal active center catalyst that has been reduced.
[0116] (5-7) Following the steps (5-7) of Example 1, HDPE hollow resin of Comparative Example 2 was obtained.
[0117] Comparative Example 3
[0118] The HDPE hollow resin of Comparative Example 3 was prepared using the following steps. The difference between Comparative Example 3 and Example 1 is that the type of fluorine source is different in step (2). The fluorine modifier composed of trifluoroacetic acid and perfluorooctanoic acid is replaced with the inorganic fluoride salt NH4HF2. The other steps are the same as in Example 1:
[0119] (1) Follow the steps (1) of Example 1.
[0120] (2) Weigh chromium acetate and chromium titanate according to the mass ratio of chromium acetate to chromium titanate of 1:15, add inorganic fluoride salt NH4HF2, and control the total fluorine content to 0.05wt%. Add chromium acetate, chromium titanate and NH4HF2 to tetrahydrofuran and / or hexane, stir and disperse to obtain a dispersion.
[0121] (3-7) Following the steps (3-7) of Example 1, HDPE hollow resin of Comparative Example 3 was obtained.
[0122] Comparative Example 4
[0123] The HDPE hollow resin of Comparative Example 4 was prepared using the following steps. The difference between Comparative Example 4 and Example 1 is that the polymerization process in steps (5) and (6) is different. The two-stage narrow temperature-controlled polymerization was changed to a single-stage polymerization without narrow temperature control. The other steps are the same as in Example 1:
[0124] (1-4) The chromium metal active center catalyst was obtained by following the steps (1-4) of Example 1.
[0125] (5) Weigh the chromium metal active center catalyst obtained in step (4) at 0.03 wt% of the total feed mass of ethylene and 1-hexene. Then, mix the weighed chromium metal active center catalyst with isobutane solvent at a ratio of 400 g / L and feed it into the polymerization reactor. Supply ethylene and 1-hexene to the polymerization reactor for a first-stage polymerization. The 1-hexene supplied to the polymerization reactor is 0.7 mol% of the total molar amount of ethylene and 1-hexene supplied to the polymerization reactor. The first-stage polymerization temperature is 75℃ and is controlled according to a wide temperature control mode of ±0.4℃ to obtain the polymer resin slurry.
[0126] (6) The polymer resin slurry obtained in step (5) is subjected to flash evaporation, deactivation and drying in sequence to obtain polymer resin powder; 1010 / FS042 composite antioxidant is added to the obtained polymer resin powder, the mass ratio of 1010 to FS042 is 10:2, and the amount of composite antioxidant added is 0.06 parts; then it is extruded and granulated at 210℃ to obtain HDPE hollow resin of Comparative Example 4.
[0127] Comparative Example 5
[0128] The HDPE hollow resin of Comparative Example 5 was prepared using the following steps. The difference between Comparative Example 5 and Example 1 is that the temperature control precision of the two polymerization stages in steps (5) and (6) is different. The two narrow temperature control stages are adjusted to two wide temperature control stages. The other steps are the same as those in Example 1:
[0129] (1-4) The chromium metal active center catalyst was obtained by following the steps (1-4) of Example 1.
[0130] (5) Weigh the chromium metal active center catalyst obtained in step (4) at 0.03 wt% of the total feed mass of ethylene and 1-hexene. Mix the weighed chromium metal active center catalyst with isobutane solvent at a ratio of 400 g / L and feed it into a first-stage reactor. Supply ethylene and 1-hexene to the first-stage reactor for first-stage polymerization. The 1-hexene supplied to the first-stage reactor is 0.4 mol% of the total molar amount of ethylene and 1-hexene supplied to the first-stage reactor. The first-stage polymerization temperature is 75±4℃, and the first-stage polymerization product is obtained.
[0131] (6) The first-stage polymerization product obtained in step (5) is flash-evaporated and then fed into the second-stage reactor. Ethylene and 1-hexene are supplied to the second-stage reactor to continue the second-stage polymerization. The 1-hexene supplied to the second-stage reactor is 1.0 mol% of the total molar amount of ethylene and 1-hexene supplied to the second-stage reactor. The second-stage polymerization temperature is 73±4℃, and a polymer resin slurry is obtained. The ratio of the total molar amount of ethylene and 1-hexene supplied to the first-stage reactor to the total molar amount of ethylene and 1-hexene supplied to the second-stage reactor is 1:2.
[0132] (7) Follow the steps (7) of Example 1 to obtain HDPE hollow resin of Comparative Example 5.
[0133] Comparative Example 6
[0134] The HDPE hollow resin of Comparative Example 6 was prepared using the following steps. The difference between Comparative Example 6 and Example 1 is that the chromium source in step (2) is different. The chromium source, which is a combination of chromium acetate and chromium titanate, is replaced with a single chromium acetate. The other steps are the same as in Example 1:
[0135] (1) Follow the steps (1) of Example 1.
[0136] (2) Weigh chromium acetate as the single chromium source. Weigh trifluoroacetic acid and perfluorooctanoic acid according to a mass ratio of trifluoroacetic acid to perfluorooctanoic acid of 1:2, and control the total fluorine content to 0.05wt%. Add chromium acetate, trifluoroacetic acid and perfluorooctanoic acid to tetrahydrofuran and / or hexane, stir and disperse to obtain a dispersion.
[0137] (3) The catalyst support was obtained by following step (3) of Example 1.
[0138] (4) The catalyst loading obtained in step (3) is transferred to a calcination furnace and calcined and activated at 840°C for 6 hours. The activation temperature is controlled with an accuracy of ±0.3°C. No reduction treatment is performed after calcination and activation to obtain a chromium metal active center catalyst with a single chromium acetate source.
[0139] (5-7) Following the steps (5-7) of Example 1, HDPE hollow resin of Comparative Example 6 was obtained.
[0140] Comparative Example 7
[0141] The HDPE hollow resin of Comparative Example 7 was prepared using the following steps. The difference between Comparative Example 7 and Example 1 is that the 1-hexene was added in steps (5) and (6) in a different way. In Comparative Example 7, the 1-hexene was added in one step without segmentation. The other steps were the same as in Example 1.
[0142] (1-4) The chromium metal active center catalyst was obtained by following the steps (1-4) of Example 1.
[0143] (5) Weigh the chromium metal active center catalyst obtained in step (4) at 0.03 wt% of the total feed mass of ethylene and 1-hexene. Then, mix the weighed chromium metal active center catalyst with isobutane solvent at a ratio of 400 g / L and feed it into a first-stage reactor. Supply ethylene and 1-hexene to the first-stage reactor for first-stage polymerization. The 1-hexene supplied to the first-stage reactor is 1.4 mol% of the total molar amount of ethylene and 1-hexene supplied to the first-stage reactor. All of the 1-hexene is added in the first-stage polymerization. The first-stage polymerization temperature is 75±0.5℃ to obtain the first-stage polymerization product.
[0144] (6) The first-stage polymerization product obtained in step (5) is flash-evaporated and then fed into the second-stage reactor for further second-stage polymerization. The second-stage polymerization temperature is 73±0.5℃. No 1-hexene is added during the second-stage polymerization, resulting in a polymer resin slurry. The ratio of the total molar amount of ethylene and 1-hexene supplied to the first-stage reactor to the total molar amount of ethylene and 1-hexene supplied to the second-stage reactor is 1:2.
[0145] (7) Follow the steps (7) of Example 1 to obtain HDPE hollow resin of Comparative Example 7.
[0146] Comparative Example 8
[0147] The HDPE hollow resin of Comparative Example 8 was prepared using the following steps. The difference between Comparative Example 8 and Example 1 is that the order of adding 1-hexene in steps (5) and (6) is different. The method of adding a low amount in the first stage and a high amount in the second stage in Example 1 is adjusted to adding a high amount in the first stage and a low amount in the second stage. The other steps are the same as those in Example 1.
[0148] (1-4) The chromium metal active center catalyst was obtained by following the steps (1-4) of Example 1.
[0149] (5) Weigh the chromium metal active center catalyst obtained in step (4) at 0.03 wt% of the total feed mass of ethylene and 1-hexene. Then, mix the weighed chromium metal active center catalyst with isobutane solvent at a ratio of 400 g / L and feed it into a first-stage reactor. Supply ethylene and 1-hexene to the first-stage reactor for first-stage polymerization. The 1-hexene supplied to the first-stage reactor is 1.0 mol% of the total molar amount of ethylene and 1-hexene supplied to the first-stage reactor. The first-stage polymerization temperature is 75±0.5℃, and the first-stage polymerization product is obtained.
[0150] (6) The first-stage polymerization product obtained in step (5) is flash-evaporated and then fed into the second-stage reactor. Ethylene and 1-hexene are supplied to the second-stage reactor to continue the second-stage polymerization. The amount of 1-hexene supplied to the second-stage reactor is 0.4 mol% of the total molar amount of ethylene and 1-hexene supplied to the second-stage reactor. The second-stage polymerization temperature is 73 ± 0.5 °C, and a polymer resin slurry is obtained. The ratio of the total molar amount of ethylene and 1-hexene supplied to the first-stage reactor to the total molar amount of ethylene and 1-hexene supplied to the second-stage reactor is 1:2.
[0151] (7) Following step (7) of Example 1, HDPE hollow resin of Comparative Example 8 was obtained.
[0152] The HDPE hollow resins prepared in Examples 1-4 and Comparative Examples 1-8 were subjected to performance tests, and the test results are shown in Table 1. The test methods and standards are as follows:
[0153] Density test: Tested according to GB / T 1033.2-2010;
[0154] Melt flow rate test: The test was conducted in accordance with GB / T 3682.1-2018, with a test load of 2.16 kg;
[0155] Tensile yield stress test: The test was conducted in accordance with GB / T 1040-2018, using type I spline, with a tensile speed of 50 mm / min;
[0156] Tensile fracture nominal strain test: The test shall be conducted in accordance with GB / T 1040-2018, using type I spline, and the tensile speed shall be 50 mm / min;
[0157] Molecular weight distribution test: The molecular weight distribution of the resin was tested by gel permeation chromatography and expressed as Mw / Mn.
[0158] Hexane extract content test: The test was conducted according to GB 4806.6-2016 "National Food Safety Standard for Food Contact Materials and Articles Part 6: Polymer Materials". A lower hexane extract content indicates a lower content of extractable low-molecular-weight substances in the resin, meaning a lower risk of plasticizer migration and leaching when the resin is used in food, beverage, and cosmetic packaging, and thus better hygiene and safety.
[0159] Table 1 Performance test results of Examples 1-4 and Comparative Examples 1-8
[0160]
[0161] As shown in Table 1, the hexane extract content of the HDPE hollow resins obtained in Examples 1-4 remained at a low level, ranging from 0.35 to 0.45 wt%. At the same time, the resin density, melt flow rate, tensile yield stress, and tensile fracture nominal strain remained within the reasonable range required for hollow resin applications. This indicates that the compound chromium source, fluorine modification, high-temperature non-reducing activation, two-stage narrow temperature-controlled polymerization, and the segmented addition of 1-hexene used in this invention have a good synergistic effect, which can reduce the content of extractable low molecular weight substances while taking into account the processing performance and mechanical properties of the resin.
[0162] Compared with Example 1, Comparative Example 1 without the addition of fluorine modifier showed a significant increase in the content of n-hexane extract and a wider molecular weight distribution, indicating that the fluorine modifier helps improve the state of the catalyst active center, making the polymerization process more conducive to reducing the formation of low molecular weight fractions.
[0163] Comparative Example 2 underwent reduction treatment after catalyst activation, resulting in a further increase in the hexane extract content of the resin, accompanied by an increase in melt flow rate and a decrease in tensile yield stress. This indicates that the reduction treatment weakens the regulatory effect of the catalyst system of the present invention on the molecular structure of the resin, which is not conducive to obtaining hollow resin with both low extract content and good mechanical properties.
[0164] In Comparative Example 3, after replacing the organic acid-type fluorine modifier with an inorganic fluorine salt, the content of the n-hexane extract remained at a high level, indicating that the form of the fluorine source affects the catalyst loading and the state of the activated active center. The organic acid-type fluorine modifier is more suitable for the system of this invention.
[0165] Comparative Example 4 used a single-stage polymerization method, and the content of n-hexane extract was higher than that in Example 1, indicating that a single polymerization stage is difficult to fully take into account both the distribution of comonomers and the molecular chain growth process. Two-stage polymerization is more conducive to reducing extractable oligomers.
[0166] Although Comparative Example 5 still used two-stage polymerization, the content of n-hexane extract increased significantly after the temperature control precision was relaxed, the molecular weight distribution also widened significantly, and the mechanical properties decreased. This indicates that stable control of polymerization temperature is crucial to reducing the formation of low molecular weight fractions.
[0167] Comparative Example 6 uses chromium acetate as a single chromium source. The resulting resin has a higher hexane extract content, but its tensile yield stress and overall balance are not as good as those in the Example. This indicates that the combination of chromium acetate and chromium titanate is more conducive to the formation of a suitable distribution of catalytic active centers, so that the resin can achieve a better balance between low extract content and mechanical properties of hollow products.
[0168] Comparative Example 7 added all of 1-hexene in one stage, while Comparative Example 8 added 1-hexene in stages but with a higher concentration in the first stage and a lower concentration in the second stage. Both examples had higher n-hexane extract contents than Example 1, indicating that 1-hexene not only needs to be added in stages, but also needs to be controlled in a way that the first stage is lower and the second stage is higher in order to better regulate the distribution of comonomers and molecular chain structure.
[0169] In summary, this invention, through the synergistic control of catalyst composition, fluorine modification method, activation method, two-stage narrow temperature-controlled polymerization, and segmented addition of 1-hexene, enables HDPE hollow resin to effectively reduce the content of n-hexane extract while maintaining good processing and mechanical properties. This makes it more suitable for hollow packaging products with high hygiene requirements, such as food, beverages, purified water, pharmaceuticals, and cosmetics.
[0170] The specific embodiments described herein are merely illustrative of the spirit of the invention. Those skilled in the art to which this invention pertains may make various modifications or additions to the described specific embodiments or use similar methods to substitute them without departing from the spirit of the invention or exceeding the scope defined by the appended claims.
Claims
1. A method for preparing HDPE hollow resin with low n-hexane extract content, characterized in that, Includes the following steps: (1) Pre-calcining 10-50 μm SiO2 porous powder at 700-900 °C for 3-5 h to obtain silica support; Chromium acetate, chromium titanate, and fluorine modifier are dispersed in an inert solvent and then mixed with the silica support and impregnated for 12–24 h. After impregnation, the mixture is dried at 70–80 °C for 4–6 h to obtain the catalyst precursor. The fluorine modifier is a combination of trifluoroacetic acid and perfluorooctanoic acid, and the inert solvent is selected from any one or more of tetrahydrofuran and hexane; The mass ratio of chromium acetate to chromium titanate is 1:10 to 1:30, and the total chromium content in the chromium acetate and chromium titanate is 0.3 to 1.0 wt% of the mass of silicon dioxide, calculated as elemental chromium. The mass ratio of trifluoroacetic acid to perfluorooctanoic acid is 1:1 to 1:5, and the total fluorine content in the fluorine modifier is 0.03 to 0.07 wt% of the mass of silicon dioxide, calculated as elemental fluorine. The catalyst precursor was calcined and activated at 800–880 °C for 5–8 h to obtain a fluorine-modified chromium metal active center catalyst. (2) Before the polymerization, the fluorine-modified chromium metal active center catalyst is mixed with isobutane, and the amount of the fluorine-modified chromium metal active center catalyst added is 300-600 g / L based on the volume of isobutane. The amount of the fluorine-modified chromium metal active center catalyst added is 0.025–0.04 wt%, based on the total feed amount of ethylene and 1-hexene. In the presence of the fluorine-modified chromium metal active center catalyst, ethylene and 1-hexene are fed into a first-stage reactor, and a first-stage polymerization is carried out at 70-90°C to obtain a first-stage polymerization product. Specifically, based on the total molar amount of ethylene and 1-hexene supplied to the first-stage reactor, the amount of 1-hexene added in the first-stage polymerization is 0.3–0.6 mol%; The first-stage polymerization product is flash-evaporated and then fed into a second-stage reactor. Ethylene and 1-hexene are supplied to the second-stage reactor for second-stage polymerization. The total molar amount of ethylene and 1-hexene supplied to the second-stage reactor is 0.8–1.2 mol% in the second-stage polymerization. The ratio of the total molar amount of ethylene and 1-hexene supplied to the first stage reactor to the total molar amount of ethylene and 1-hexene supplied to the second stage reactor is 1:1 to 1:
3. The set temperature for the second-stage polymerization is 1-3℃ lower than that for the first-stage polymerization. The temperature control accuracy for both the first-stage and second-stage polymerization is ±0.5℃, resulting in a polymerized resin. (3) Granulate the polymer resin to obtain the HDPE hollow resin with low n-hexane extract content.
2. The preparation method according to claim 1, characterized in that, In step (3): The process before granulation also includes a post-processing step, which includes flash evaporation, deactivation, and drying. And / or, the granulation temperature is 190–230°C.
3. The preparation method according to claim 1, characterized in that: An antioxidant system is added before granulation, wherein the antioxidant system comprises any one or more of hindered phenolic antioxidants and hydroxylamine antioxidants; The amount of antioxidant system added is 0.05 to 0.08 parts by weight per 100 parts by weight of polymeric resin.
4. The preparation method according to claim 3, characterized in that: When the antioxidant system contains both hindered phenolic antioxidants and hydroxylamine antioxidants, the mass ratio of the hindered phenolic antioxidants to the hydroxylamine antioxidants is 10:1 to 10:
5. And / or, the hydroxylamine antioxidant is N,N-bis(n-octadecane)hydroxylamine; And / or, the hindered phenolic antioxidant is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate].
5. An HDPE hollow resin, characterized in that, It is prepared by the preparation method according to any one of claims 1 to 4.
6. A hollow product, characterized in that, It includes the HDPE hollow resin as described in claim 5.
Citation Information
Patent Citations
Titanium fluoride modified load type chrome alum double-active center catalyst and preparation method thereof
CN105199021A
Polyethylene resin for hollow product, and composition and preparation method thereof
CN112679641A